Green Marketing in Sustainable Business: Utilizing Fly Ash as a Cement Substitute to Reduce CO2 Emissions in the Mortar Industry - Setya Negara, Ade Irma; Destiana Tunggal Pramesti; Muhammad Sodikun (HM Publisher, 2024)
Green marketing has become increasingly important in efforts to achieve sustainable business, especially in the mortar industry. The use of fly ash as a cement substitute has emerged as a technological innovation aimed at reducing CO2 emissions in mortar production. This research explores the close relationship between green marketing and the use of fly ash in this industry, as well as its impact on business sustainability. Through analysis of green marketing strategies, the use of fly ash in mortar composition, and the associated environmental impacts, this research aims to provide in-depth insight into how sustainable business practices and technological innovation can collaborate in creating environmentally friendly products. By focusing on this research, companies can advance their efforts to reduce CO2 emissions while strengthening their corporate image as an entity that cares about the environment and is committed to sustainability. This research promotes efforts to replace conventional practices with more sustainable and environmental approaches, leading to broader benefits for our planet and society as a whole.